O programa de formação de professores alfabetizadores – PROFA – e suas implicações pedagógicas: concepção de alfabetização, atuação profissional e resultados obtidos - Campos, Rosariane Glaucia Mendonça (2006)
This work is based on an investigation about a formation program for teachers of literacy (PROFA), in accordance with Ministry Education s ongoing formation of the elementary teaching secretariat policy, because of the teaching reform introduced in Fernando Henrique Cardoso s term of office. The program consist of a course for the development of teachers competence as well as goals, contents and literacy methodologies of the teachers program based on Emília Ferreiro s construtivism conception under the coordination of Telma Weisz. It aims particularly at the enhancement of the teaching learning process of the students. The goal of this research is to observe the effects on these literacy practice together with the results on the students learning by comparing the data and also, PROFA s theorectical guidelines and methodologies, the work developed by teachers of literacy in the classroom in order to investigate whether or not the program reached its goals. As a procedure a qualitative research is used in the investigation of the pedagogical practice of four PROFA s teachers, the observation of their practice, as well as some interviews with teachers, coordinators involved in this process, and also a documental analysis of different registers which qualify the study case. It is intended to observe some social, cultural and contextual elements that may or may not influence the teachers practice and the students learning.